Industry use of evidence to influence alcohol policy: a case study of submissions to the 2008 Scottish government consultation. - Jim McCambridge; Ben Hawkins; Chris Holden (PLoS Medicine, 2013)
Jim McCambridge and colleagues analyze industry submissions to a Scottish Government consultation on whole-population approaches to alcohol policy.